Beyond the black and white: female domestic servants, dress and identity in France and Britain, 1900-1939 - Louvier, F (Taylor and Francis, 2019)
Far from being a trivial detail, clothes fundamentally define who we are and how we are perceived by others. Drawing on a large sample of French and British servants’ memoirs, this article explores how dress served a crucial but contrasting role in the way French and British servants articulated their identities within and outside the home between 1900 and 1939. It argues that servants’ dress was deeply linked to the nature of the occupation in each country and the structure of their respective female labour markets.